Transforming Growth Factor Beta 1 Augments Calvarial Defect Healing and Promotes Suture Regeneration - Shakir, Sameer (Tissue Eng Part A, 2015)
Background: Repair of complex cranial defects is hindered by a paucity of appropriate donor tissue. Bone morphogenetic protein 2 (BMP2) and transforming growth factor beta 1 (TGFβ1) have been shown separately to induce bone formation through physiologically distinct mechanisms and potentially improve surgical outcome for cranial defect repair by obviating the need for donor tissue. We hypothesize that a combination of BMP2 and TGFβ1 would improve calvarial defect healing by augmenting physiologic osteogenic mechanisms. Methods/Results: Coronal suturectomies (3×15 mm) were performed in 10-day-old New Zealand White rabbits. DermaMatrix™ (3×15mm) patterned with four treatments (vehicle, 350 ng BMP2, 200 ng TGFβ1, or 350 ng BMP2+200 ng TGFβ1) was placed in suturectomy sites and rabbits were euthanized at 6 weeks of age. Two-dimensional (2D) defect healing, bone volume, and bone density were quantified by computed tomography. Regenerated bone was qualitatively assessed histologically. One-way analysis of variance revealed significant group main effects for all bone quantity measures. Analysis revealed significant differences in 2D defect healing, bone volume, and bone density between the control group and all treatment groups, but no significant differences were detected among the three growth factor treatment groups. Qualitatively, TGFβ1 treatment produced bone with morphology most similar to native bone. TGFβ1-regenerated bone contained a suture-like tissue, growing from the lateral edge of the defect margin toward the midline. Unique to the BMP2 treatment group, regenerated bone contained lacunae with chondrocytes, demonstrating the presence of endochondral ossification. Conclusions/Significance: Total healing in BMP2 and TGFβ1 treatment groups is not significantly different. The combination of BMP2+TGFβ1 did not significantly increase bone healing compared with treatment with BMP2 or TGFβ1 alone postoperatively at 4 weeks. We highlight the potential use of TGFβ1 to regenerate calvarial bone and cranial sutures. TGFβ1 therapy significantly augmented bony defect healing at an earlier time point when compared with control, regenerated bone along the native intramembranous ossification pathway, and (unlike BMP2 alone or in combination with TGFβ1) permitted normal suture reformation. We propose a novel method of craniofacial bone regeneration using low-dose, spatially controlled growth factor therapies to minimize potentially harmful effects while maximizing local bioavailability and regenerating native tissues.